Investigation of laccase activity in cholinium-based ionic liquids using experimental and molecular dynamics techniques - Chan, Kam Khong (2024)
Laccases hold great potential for biotechnological applications, particularly in environmental pollutant remediation. Laccase activity is governed by the solvent environment, and ionic liquids (ILs) emerge as a versatile solvent for activation or stabilization of enzymes. Herein, effects of cholinium-based ILs formulated with carboxylic acids, inorganic acid, and amino acids as anionic species, on the catalytic activity of laccase from Trametes versicolor were investigated by experimental and computational approaches. Experimental results showed that laccase activity was enhanced by 21.39 % in 0.5 M cholinium dihydrogen citrate ([Cho][DHC]), in relation to the laccase activity in phosphate buffer medium. However, cholinium aminoate ILs negatively affected laccase activity, as evidenced by the partial deactivation of laccase in both cholinium glycinate and cholinium phenylalaninate, at concentrations of 0.1 M and 0.5 M, respectively. Molecular dynamics studies revealed that the enhancement of laccase activity in [Cho][DHC] might be attributed to the highly stabilized and compact structure of laccase, facilitating a better internal electron transfer during the laccase-substrate interactions. Enhanced catalytic performance of laccase in [Cho][DHC] was postulated to be driven by the high accumulation level of dihydrogen citrate anions around laccase's surface. [Cho][DHC] holds great promise as a cosolvent in laccase-catalyzed biochemical reactions.